A new model approximating M/PH/1 queuing systems during the transient period - Gao, H.; Lynch, M. A. M. (Mathematical Modelling and Analysis, 2001)
This paper presents an efficient approximation for M/PH/1 queuing systems based on the replacement of the majority of the vector valued state probabilities by a diffusion approximation. The strength of the new approximation is that it gives more accurate results than the current diffusion approximations at both high and low traffic intensities and at little extra computational cost. The accuracy of the new approximation during the transient is shown by comparing it numerically with solutions to the M/PH/1 system and current approaches based on the diffusion approximation. Masinio aptarnavimo sistemos M/PH/1 aproksimavimo perėjimo periodu naujas modelis Santrauka. Straipsnyje pateikta efektyvi masinio aptarnavimo sistemos M/PH/1 aproksimacija, kuri gaunama naudojant daugumos būsenų tikimybių difuzinę aproksimaciją. Šios aproksimacijos privalumas tas, kad gaunami tikslesni rezultatai, negu naudojant įprastines difuzines aproksimacijas, tiek esant mažiems, tiek dideliems paraiškų intensyvumui. Be to, pakanka mažiau skaičiavimu. Šios naujos aproksimacijos tikslumas perėjimo būsenoje parodomas lyginant sistemos M/PH/1 sprendinius su sprendiniais, kurie gaunami naudojant įprastinę difuzinę aproksimaciją. First Published Online: 14 Oct 2010